2019
DOI: 10.1177/1046496419827376
|View full text |Cite
|
Sign up to set email alerts
|

Team Dispersion and Performance: The Role of Team Communication and Transformational Leadership

Abstract: Organizations increasingly rely on virtual teams to access geographically dispersed expertise. Yet, team dispersion introduces challenges to team communication that may negatively influence team performance. Using a sample of 53 innovation teams representing a variety of geographic dispersion configurations from completely collocated to highly dispersed, we examined the moderating role of transformational leadership on the relationship between team dispersion, team communication, and team performance. Our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 105 publications
(163 reference statements)
4
79
0
2
Order By: Relevance
“…Also, VT leadership research suggests that team leaders need to stop seeing themselves as heroic leaders, but instead, need to redefine their roles (e.g., facilitators of the members' initiatives) to improve VT performance (Hoegl & Muethel, ). As researchers pointed out, transformational leadership may not be applicable for geographically dispersed teams, fostering leadership among VT members may be more effective (Eisenberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, VT leadership research suggests that team leaders need to stop seeing themselves as heroic leaders, but instead, need to redefine their roles (e.g., facilitators of the members' initiatives) to improve VT performance (Hoegl & Muethel, ). As researchers pointed out, transformational leadership may not be applicable for geographically dispersed teams, fostering leadership among VT members may be more effective (Eisenberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…shared (Han et al, 2018), transformational (Eisenberg et al, 2019) or identity (Smith et al, 2018) leadership approaches may be useful).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of non-verbal cues and the geographical distance are some of the reasons for distrust in virtual teams. Trust between team members will generate optimal decision making [14]. Research found a positive effect of trust on VT decision-making processes [38,39].…”
Section: Literature Reviewmentioning
confidence: 99%